VARIANT FORMATION OF MEDIAN NERVEA REVIEW OF LITERATURE - B. SADANANDA RAO; V.LEELA (International Journal of Pharma and Bio Sciences, 2013)
Anatomical variations of median nerve are frequent. Anomalies of the brachial plexus and its terminal branches are also common. An extra lateral root was observed arising from the lateral cord of brachial plexus, in the left axilla of a male cadaver during the course of undergraduate gross anatomy dissections. This anomalous root had a very oblique course over the axillary artery. The application and significance of our finding vis-à-vis current research in basic & clinical medicine, is discussed.